2017
DOI: 10.1088/1748-605x/aa4eb7
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic bone formation by gel-derived bioactive glass-poly-L-lactide-co-glycolide composites in a rabbit muscle model

Abstract: In this study we aimed to assess the in vivo osteoinductive properties of two composite scaffolds made of PLGA (poly-L-lactide-co-glycolide) and two types of gel-derived bioactive glasses, namely a high silica S2 bioactive glass (S2-PLGA composites) or high lime A2 bioactive glass (A2-PLGA composites). To achieve that, the potential of the composites to induce ectopic bone formation in a rabbit muscle has been examined along with the control PLGA scaffold. Cylinder-like scaffolds of 7  ×  3 mm (width  ×  heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Verification of selected scaffolds was done in a rabbit model, basically as previously described [27]. This study was approved by the local Ethical Committee of the Jagiellonian University, decision no.…”
Section: In Vivo Ectopic Bone Formation and Histologymentioning
confidence: 99%
“…Verification of selected scaffolds was done in a rabbit model, basically as previously described [27]. This study was approved by the local Ethical Committee of the Jagiellonian University, decision no.…”
Section: In Vivo Ectopic Bone Formation and Histologymentioning
confidence: 99%
“…Compared to PLGA alone, the composite scaffolds gradually degraded as bone formation took place and were more effective at inducing ectopic bone formation. The presence of osteoblast-like and osteoclast-like cells was noted in the vicinity of the scaffolds, confirmed by immunohistochemical staining for osteocalcin, bone morphogenetic protein-2 (BMP-2), and cathepsin K [48]. compared to uncoated S53P4 (Figure 3) [49].…”
Section: Plga Pcl and Other Synthetic Polymersmentioning
confidence: 81%
“…Examining early osteogenic transcription factors showed that the expression levels of Runx-2 and Osx were generally higher for cells cultured on the scaffolds without P Ectopic bone formation is a standard procedure to verify osteoinductivity of materials [30]. Previously, we examined osteoinductive potential of selected scaffolds of SiO 2 -CaO-P 2 O 5 system, namely A2/PLGA and S2/PLGA composites, and both scaffolds were more effective at inducing ectopic bone formation in a rabbit muscle compared to plain PLGA [27]. Giving that our in present in vitro studies the scaffolds depleted of P 2 O 5 , i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Veri cation of selected scaffolds was done in a rabbit model, basically as previously described [27]. This study was approved by the local Ethical Committee of the Jagiellonian University, decision no.…”
Section: In Vivo Ectopic Bone Formation and Histologymentioning
confidence: 99%